Integrating Digital Books, 3D Animations, and Online Problem-based Learning to Improve Pre-service Teachers’ Scientific Literacy in General Physics Course - Sunarti, Titin; Satriawan, Muhammad; Prahani, Binar Kurnia; Rizki, Iqbal Ainur (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2024)
Some literature suggests that the low scientific literacy of pre-service teachers (PSTs) should be considered when designing teaching strategies. To address this issue, digital books with 3D animation, representing advanced developments in digital technology, can be integrated into an online Problem-Based Learning (PBL) model. Consequently, this study aimed to test the effectiveness of the Digital Books, 3D animation, and PBL (DBAPBL) model in enhancing the scientific literacy of PSTs. The research method employed was quantitative, utilizing a quasi-experimental design. The sample comprised 67 pre-service biology teachers enrolled in the General Physics course. Data collection technique utilised pre- and post-test along with survey in the last teaching session. Then, the data was analysed descriptively and statistically using t-test. The findings revealed that the DBAPBL model led to PSTs achieving a science literacy score above 89.5 or in the high category. Statistical test results also indicated a significant difference between scientific literacy's pre- and post-test results, affirming the model's effectiveness. Another noteworthy finding suggests that PSTs have a tendency to respond positively to the DBPAPBL model. This research implies a pedagogical innovation in physics education and advocates for updating curriculum guidelines related to the DBAPBL model, thereby contributing to the improvement of Indonesia's PISA scores.